The Role and Challenges of E-Medical Records Implementation in Indonesia's Health System: Legal and Technological Perspectives - Novita Badiningsih (Jurnal Sehat Indonesia (JUSINDO), 2026)
The digital literacy gap among medical personnel is a challenge, and the lack of understanding and skills in using information technology may hinder the effective utilization of e-medical records. The purpose of this study is to analyze the impact of e-medical records on the efficiency of health services, as well as evaluate the legal aspects governing their use in Indonesia. This research method uses normative juridical and empirical juridical research approaches; the research subjects consist of medical personnel, hospital managers, and IT system developers. In this research, the legal material collection technique that will be used is the literature collection technique. Overall, although e-medical records present challenges related to data security and privacy that must be addressed seriously, the development of a more comprehensive and clear legal framework will be essential to support the growth of this system as well as protect the rights of patients in the digital era; further regulatory development is still needed to optimize the benefits and overcome the challenges. There is a need for strategic planning that includes a thorough needs assessment, a realistic timeline, and adequate budget allocation; ongoing training for staff; establishment of an internal technical support team and mentoring program for users; and evaluation and monitoring with regular KPI measurement.